Growth And Yield of Two Varieties of Sorghum (Sorghum bicolour L. Moench) Through Rice Husk Organic Fertilizer Application - Nurmi, Nurmi; Syamsul Bahri; Yundriyani; Yunnita Rahim; Mohamad Arief Azis (International journal of technology and education research, 2025)
The study aims to determine the effect of organic rice husk fertilizer on the growth and yield of sorghum plants (Sorghum bicolor L. Moench). This study used a Randomized Block Design (RBD) with the first factor being sorghum plant varieties (V) consisting of 2 levels: the Numbu variety and the Kawali variety. The second factor was rice husk fertilizer (P) consisting of 3 levels: no fertilizer (control). 25 tons ha-1 of rice husk fertilizer. and 50 tons ha-1 of rice husk fertilizer. repeated 3 times. The results of the study showed that there was an interaction between the treatment of variety type and organic fertilizer dose on the parameters of plant height. number of leaves and seed weight of sorghum planting and there was no interaction on panicle length. but singly the treatment of variety type and organic fertilizer dose did not provide a significant effect on the parameters of plant height. number of leaves and panicle length. but did provide a significant effect on sorghum seed weight. The best sorghum plant production results were found in the treatment of the Numbu variety type with an organic fertilizer dose of 50 tons ha-1.